ANALISIS TEORI KOGNITIF DALAM MENINGKATKAN KREATIVITAS GURU PAI PADA IMPLEMENTASI KURIKULUM MERDEKA BELAJAR - Hidayati Fauziah, Hilda; Ghaida Muthmainnah, Hasna; Chadidjah, Sitti (IAIN Madura, 2025)
In the context of education in Indonesia, Merdeka Belajar Curriculum comes as an innovative step to create flexible, relevant, and learner-centered learning. The Merdeka Curriculum encourages teachers to become creative learning facilitators, so that they can optimally meet students' needs and potential. In an effort to increase teacher creativity, cognitive theory emphasizes understanding the thinking process, problem solving, and developing new ideas, which are closely related to creativity in learning. The method used is to collect and analyze information from various journals and articles related to the theme of teacher creativity and cognitive theory, with the data the data can see bener really valid. then presented the results obtained in the results. The result of this research is that by collecting and analyzing various relevant references. Two things are the main focus in this study, namely the perspective of cognitive theory and its relationship with teacher creativity in implementing the Merdeka Belajar Curriculum. In this context, cognitive theory plays an important role in helping teachers understand how students think and learn, so that they can design more effective and creative learning.